The Nexus of Economic Growth, Human Development Index, and Unemployment to Income Inequality in East Java - Octavia, Elyada Christi; Firmansyah, Arif Amanudin; Fatmala, Rahmania Dwi; Aisa, Siti Nur; Ma'ruf, Aminudin; Hamzah, Akhmad Faisal (Economics Departement, Faculty of Business and Economics, Universitas Surabaya, 2024)
The research seeks to analyse the complex correlation between economic growth, human development index, and unemployment on income inequality in East Java from 2018 to 2022. This study addresses the issue of inequality in East Java both theoretically and empirically. The data is obtained from the Central Agency of Statistics and the Regional Development Planning Agency of East Java Province. Through specific considerations, this study utilized panel data from the six districts or cities with the highest and lowest income inequality. The data analysis employs panel data regression with the selected model, the Common Effect Model, to examine the influence among variables. Furthermore, in describing the results of the analysis, descriptive and quantitative methods are used. The analysis shows that the three exogenous variables collectively influence income inequality. Through the T-test, it was discovered that only the human development index variable shows a significant effect on income inequality. On the contrary, economic growth and unemployment variables show no significant effect. However, all three positively correlate with income inequality in East Java from 2018 to 2022.